ANALISIS KESULITAN MENERJEMAH TEKS BAHASA ARAB PADA MATA KULIAH TARJAMAH DI INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA TAHUN 2024 - Mahfudlon, Mahfudlon; Fanirin, Hasyim; Arifin, Mas’ud (Sindoro: Cendikia Pendidikan, 2024)
The aim of this research is to obtain accurate data regarding the translation process, discover the difficulties faced by students in translating, and find out the steps taken to overcome difficulties translating Arabic. This research method uses a qualitative approach with data collection techniques in the form of observation, documentation and interviews with Arabic Language Education study program students and also lecturers who teach tarjamah courses. The results of the research show: 1) The process of translating Arabic in tarjamah courses at IAI AL-AZIS is carried out in various ways, such as lecturers recording voices and giving them to students to write and translate, also by forming small groups and then presenting or translating Arabic texts, then the lecturer corrects the reading from the student's translation results, after discussing the Arabic text and providing teaching regarding qawaid related to the Arabic text being studied. 2) The difficulties experienced by students during the process of translating Arabic texts can be divided into two parts, namely linguistic factors and non-linguistic factors. The linguistic factors in question are: morphological factors, syntactic factors, semantic factors and also restructuring factors. Meanwhile, non-linguistic factors include: internal factors and external factors. Key Words: Difficulty Translating, Arabic,Tarjamah Courses.